Pemikiran Fikih Ekonomi Ibnu Hazm tentang Kesejahteraan Tenaga Kerja - Muh Said HM (Institut Agama Islam Negeri Madura, 2016)
Ibn Hazm (384-456 H / 994-1064 AD) is one of the great theologian of brilliant, well-known in Islamic thinking in the Islamic world at the beginning of X century AD in Andalusia (Spain). Mastery of science multi-disciplinary, always encouraging and natural coloring of his thoughts. The various of popular designation as scientists and theologian figure attached to him, in addition to designation as a figure of Islamic economists. However, the realm of his thoughts particularly in the field of Islamic Economics Jurisprudence, can not be undoubted as a scientific contribution in the field of Islamic economics to this day. Fulfillment of human rights with regard to the needs of the economy and life welfare, particularly in this case among the labor, is something that is required to be realized by the government, the businessman in accordance with agreement of work contract.